[PP.27.22] SUPPRESSION OF ALDOSTERONE SECRETION AFTER RECUMBENT SALINE INFUSION DOES NOT EXCLUDE LATERALIZED PRIMARY ALDOSTERONISM. (September 2017) - Cornu, E.; Steichen, O.; Nogueira-Silva, L.; Pagny, Jy.; Grataloup, C.; Baron, S.; Zinzindohoue, F.; Plouin, Pf.; Amar, L.
Abstract : Objective: Guidelines recommend suppression tests such as the saline infusion test (SIT) to ascertain the diagnosis of primary aldosteronism (PA) in patients with a high aldosterone:renin ratio. However, suppression tests have only been evaluated in small retrospective series, and some experts consider that they are not helpful for the diagnosis of PA. In this study, we evaluated whether low post-SIT aldosterone concentrations do exclude lateralized PA. Design and method: Between February 2009 and December 2013, 199 patients diagnosed with PA on the basis of 2 elevated aldosterone:renin ratio results and a high basal plasma or urinary aldosterone level or high post-SIT aldosterone level had a selective adrenal venous sampling. We used a selectivity index of 2 and a lateralization index of 4 to interpret the adrenal venous sampling results. Results: Baseline characteristics of the patients were the following (percent or median): men 63%, 48 years old, office blood pressure 142/88 mm Hg, serum potassium 3.4 mmol/L, aldosterone:renin ratio 113 pmol/mU, plasma aldosterone concentration 588 pmol/L. The proportion of patients with lateralized adrenal venous sampling was 12 of 41 (29%) among those with post-SIT aldosterone <139 pmol/L (5 ng/dL) and 38 of 104 (37%) among those with post-SIT aldosterone <277 pmol/L (10 ng/dL). Post-SIT aldosterone levels were not associated with the blood pressure outcome of adrenalectomy. Figure. No caption available. Conclusions: A low post-SIT aldosterone level cannot rule out lateralized PA, even with a low threshold (139 pmol/L). Adrenal venous sampling should be considered for patients who are eligible for surgery with elevated basal aldosterone levels even if they have low aldosterone concentrations after recumbent saline suppression testing.